First record of Anteon xericum Olmi & van Harten (Hymenoptera, Dryinidae) from Palaearctic region - Meidani, Zahra; Khayrandish, Mohammad; Olmi, Massimo; Madjdzadeh, Seyed Massoud; Moghaddam, Mostafa Ghafouri (Zootaxa, 2023)
The Malaise trap program was implemented to carry out periodic sampling in southeastern Iran, specifically targeting Kerman province, in order to investigate and study specimens belonging to the family Dryinidae. Among the assemblage of collected specimens, notable identifications were made within the subfamily Anteoninae, including the discernment of Anteon xericum Olmi & van Harten. This significant finding signifies a previously unreported occurrence in the Palaearctic region (Iran). A detailed diagnosis of the species, an identification key to Iranian Anteon species, a modified key to the Anteon females of the Eastern Palaearctic, along with a distribution map are provided.